Natural Disasters and the Reshaping of Global Value Chains - Freund, Caroline; Mattoo, Aaditya; Mulabdic, Alen; Ruta, Michele (World Bank, Washington, DC, 2021)
To understand the longer term consequences of natural disasters for global value chains, this paper examines trade in the automobile and electronic sectors after the 2011 earthquake in Japan. Contrary to widespread expectations, the analysis shows that the shock did not lead to reshoring, nearshoring, or diversification; and trade in intermediate products was disrupted less than trade in final goods. Imports did shift to new suppliers, especially where dependence on Japan was greater. But production relocated to developing countries rather than to other top exporters. Despite important differences, the observed pattern of switching may be relevant to disasters like the COVID-19 pandemic.